2008
DOI: 10.1111/j.1468-2958.2008.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Uncertainty in News Coverage of Cancer Research: Effects of Hedging on Scientists and Journalists Credibility

Abstract: News reports of scientific research are rarely hedged; in other words, the reports do not contain caveats, limitations, or other indicators of scientific uncertainty. Some have suggested that hedging may influence news consumers’ perceptions of scientists’ and journalists’ credibility (perceptions that may be related to support for scientific research and/or adoption of scientific recommendations). But whether hedging does affect audience perceptions is unknown. A multiple‐message experiment (N= 601) found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
236
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(265 citation statements)
references
References 47 publications
14
236
0
3
Order By: Relevance
“…The absence of cancer statistics in cancer news is likely a by product of the streamlining process, whereby journalists cut scientific content that is deemed lexically challenging to the audience (Jensen, 2008). If true, then change may come only as journalists are better trained to appreciate aspects of science central to effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of cancer statistics in cancer news is likely a by product of the streamlining process, whereby journalists cut scientific content that is deemed lexically challenging to the audience (Jensen, 2008). If true, then change may come only as journalists are better trained to appreciate aspects of science central to effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Although scientific communicators may stress persuasion, deliberation would be better (39). Communicating uncertainty is essential to building credibility (40,41), and trust best predicts attention to scientific experts (42).…”
Section: Climate Scientists' Presumed Agendasmentioning
confidence: 99%
“…That local and regional papers (remembering only 6 of a possible 595 UK local and regional newspapers archived by the Nexis UK database covered this story) as well as some national press, relied on the Press Association report for their stories perhaps reflects restraints on their resources, but also highlights a concern that original journalism is being lost in Newspapers in many cases did not report the complexity of the study and did not report the limitations of the research. Previous studies have shown that this is often the case, but as Jensen found in his multiple message experiment (Jensen 2008), both scientists and journalists were viewed as more trustworthy when study limitations were reported. However, the study itself was large and complex, which could prove a challenge to a busy journalist on a tight deadline.…”
Section: Resultsmentioning
confidence: 86%